O engajamento durante o processo de co-criação em workshops criativos - Vargas, Felipe Franzon (Universidade do Vale do Rio dos Sinos, 2016)
The co-creation involves different users to discover new things. The creative process consists on different phases, encompassing from the generation of ideas to the development of the final project. Thus, the co-creation process requires from the individuals abilities to develop during the phases, allowing them to integrate to the processes knowledge, sharing experiences and new capacities. The engagement is relevant not just to involve the individuals in this process, but to enable them to participate actively and in an efficient way, to aggregate value to the organization, to the project and to the participants. This study aims to identify the different elements that influence the engagement during the phases of co-creation process. For this research to be accomplished it was used workshops consisting of short creative processes, involving the intense performance of the participants in the activities. Then, the study has been divided into two stages for its implementation: an exploratory and a descriptive phase. The qualitative research consists in observing other workshops and interviews with teachers and the participants, for the recognition and perception of the study field. The quantitative research has a questionnaire based on the model study from Vivek (2009), which considers different dimensions of consumer engagement related to products, services and activities. This phase of the research aims to examine the experience of the participants, based on engagement in the co-creation process, through the workshops analyzed. In addition, reports were collected from the participants, so that they could be able to support and justify the dynamics experienced. After this process, the survey found that the intrinsic and extrinsic factors are important for the engagement, having a direct relationship through the its influence, in the context of co-creation. Furthermore, the definition of activities is very important in a workshop, assisting the performance of individuals and the way they deal with the subject. However, driving the dynamics in a creative process is what makes the difference, making it possible to promote the engagement of the participants during its different phases. The co-creation management becomes a fundamental factor to explore and to assist the development of innovation in organizations.
Keywords: Co-criação; Engajamento; Processos; Workshops; Co-creation; Engagement; Processes; ACCNPQ::Ciências Sociais Aplicadas::Administração